Engineering Heat Transfer - Annaratone, Donatello. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book is a generalist textbook; it is designed for anybody interested in heat transmission, including scholars, designers and students. Two criteria constitute the foundation of Annaratone’s books, including the present one. The first one consists of indispensable scientific rigour without theoretical exasperation The inclusion in the book of some theoretical studies, even if admirable for their scientific rigor, would have strengthened the scientific foundation of this publication, yet without providing the reader with further applicable know-how. The second criterion is to deliver practical solution to operational problems. This criterion is fulfilled through equations based on scientific rigor, as well as a series of approximated equations, leading to convenient and practically acceptable solutions, and through diagrams and tables. When a practical case is close to a well defined theoretical solution, corrective factors are shown to offer simple and correct solutions to the problem. After a brief introduction in Chapter 1, heat transfer by conduction in both steady and unsteady state is examined in Chapter 2 as well as Chapter 3. Chapter 4 develops the dimensional analysis as an indispensable premise to Chapter 5 with its focus on heat transfer by convection. Chapter 6 analyzes heat transfer by radiation including radiation by flame. Chapter 7 illustrates the required behavior when examining heat transfer in heat exchangers, as well as tube banks. Chapter 8 discusses pressure drops in detail. Appendix A shows a series of Tables relative to thermal characteristics of the materials. Appendix B includes a series of Tables about the corrective factors to be adopted to obtain the real value of the mean temperature difference in design computation. Appendix C includes a series of Tables about the corrective factors to be adopted to obtain the real value of the exit temperature of the heating fluid in verification computation.